Comparative analysis of rice grain quality and climate change impacts in temperate production zones from an Australian rice industry perspective - Fernando, Yvonne; Ovenden, Ben; Sreenivasulu, Nese; Butardo, Vito (MDPI, 2025)
Climate change poses major challenges for temperate rice production systems, with significant implications on rice grain quality, impacting the consumer markets and thus forth addressing unimpaired grain quality solutions is vital for industry profita-bility. This review synthesizes current knowledge of climate-induced quality changes in temperate-grown rice, focusing on the Australian industry as a primary case study alongside comparisons with other temperate regions. Environmental factors including temperature extremes, altered rainfall patterns, elevated CO₂, and increased salinity negatively impact key physicochemical, textural and aromatic properties of rice qual-ity classes. Different rice classes display distinct vulnerabilities that impact market value in the trade: medium-grain japonica varieties show reduced amylose content under heat stress, aromatic varieties experience altered aroma compound synthesis under drought, and long-grain types show compromised kernel integrity under com-bined stress with reduced head rice yield and increase of percent chalk. Emerging phenotyping tools, including hyperspectral imaging and machine learning, offer promising approaches for monitoring impacts and speeding adaptation. The Australi-an rice industry has built adaptive capacity through cold-tolerant breeding, precision agriculture, and water-efficient practices. However, projected scenarios of more ex-treme temperature variability and altered precipitation present continuing challenges to the temperate rice industry. This review identifies research priorities to secure high-quality rice in temperate regions under climate change and discussed the inte-grated solutions on above highlighted limiting factors.